Field Bindweed (Convolvulus arvensis) Control in Tef (Eragrostis tef (Zucc.) Trotter) through Various Herbicide Combinations - Gebrekidan Feleke; Dereje Chala; Bizuwork Tafes (International Journal of Agronomy)
Field bindweed is the major weed problem for tef producers across the central highlands of Ethiopia. Herbicide application alone or coupled with once or twice hand weeding for field bindweed control is difficult due to its biological features, labor-intensive, and time-consuming. The field trial was carried out at Debre Zeit from 2020 to 2021 cropping seasons to investigate different postemergence herbicides against the grass and broadleaf weeds, in general, and field bindweed in particular, in tef farming, using a randomized complete block design with three replications. As a result, we could see that the herbicide combination had no visible effect on durum wheat’s overall performance, which makes us recommend it for the control of field bindweed. In the sequential application, a wide spectrum of herbicides (Musket Power OD 460, Pallas 45 OD, and Sekator OD 375) were applied at tillering stage, and other selective herbicides (Derby 175 SC and 2,4-diamine salt 720 g/L 720 g/L) were applied at the heading stage, and the last nonselective herbicide (Roundup) was applied at physiological maturity of tef when the Convolvulus arvensis was regrowth naturally/latecomer weed. All postemergency herbicide treatments reduced significantly both broadleaf and grass weeds, in general, and C. arvensis infestation, in particular, when compared to the weedy control. Of these, Musket Power OD 460 at tillering stage integrated with 2,4-diamine salt 720 g/L at the heading stage was more effective than other herbicides for eliminating all weeds and C. arvensis in particular throughout the crop life. This weed management option resulted in considerably enhanced weed control efficiency and weed killing potential, reduced weed dry biomass and yield loss, improved grain yield, and economic benefit with an acceptable marginal rate of return for tef growers.